Modulation of Beta Oscillations in the Pallidum During Externally Cued Gait - Lu, Chiahao; Amundsen-Huffmaster, Sommer L.; Louie, Kenneth H.; Petrucci, Matthew N.; Palnitkar, Tara; Patriat, Remi; Harel, Noam; Park, Michael C.; Vitek, Jerrold L.; MacKinnon, Colum D.; Cooper, Scott E. (Frontiers in Signal Processing, 2022)
Freezing of gait (FOG) is a particularly debilitating symptom of Parkinson’s disease (PD) and is often refractory to treatment. A striking feature of FOG is that external sensory cues can be used to overcome freezing and improve gait. Local field potentials (LFPs) recorded from the subthalamic nucleus (STN) and globus pallidus (GP) show that beta-band power modulates with gait phase. In the STN, beta-band oscillations are modulated by external cues, but it is unknown if this relationship holds in the globus pallidus (GP). Here we report LFP data recorded from the left GP, using a Medtronic PC+S device, in a 68-year-old man with PD and FOG during treadmill walking. A “stepping stone” task was used during which stepping was cued using visual targets of constant color or targets that unpredictably changed color, requiring a step length adjustment. Gait performance was quantified using measures of treadmill ground reaction forces and center of pressure and body kinematics from video monitoring. Beta-band power (12 to 30 Hz) and number of freezing episodes were measured. Cues which unpredictably changed color improved FOG more than conventional cues and were associated with greater modulation of beta-band power in phase with gait. This preliminary finding suggests that cueing-induced improvement of FOG may relate to beta-band modulation.